Anthropology of Religion: Sighting the dynamics of sacredness - Quintero Núñez, Helmer; Jara Ramírez, Milton Andrés; Palacios Vanegas, Hector Fabian; Blanco Linares, Carlos Hugo; Quintero Núñez, Helmer; Jara Ramírez, Milton Andrés; Palacios Vanegas, Hector Fabian; Blanco Linares, Carlos Hugo; Quintero Núñez, Helmer; Jara Ramírez, Milton Andrés; Palacios Vanegas, Hector Fabian; Blanco Linares, Carlos Hugo (Corporación Universitaria Americana, 2024)
Introduction: the sciences of religion have been involved in the understandings of transcendence and its derived relations. Objective: the present study recognizes the theoretical considerations held by the anthropology of religion on the dynamics of sacredness. Methodology: the study employed hermeneutics applying deductive technique. Result: the study identified the anthropological character of religion, its structure, and the notion of the sacred and the profane. Conclusion: The conceptions allow to assume that it is necessary to assume the manifestations of religiosity and spirituality in the understandings of the current social and cultural systems.